The development of a rapid test for vascular endothelial growth factor (VEGF) detection and the effects of VEGF and anti-VEGF on permeability of endothelial cells - Lim, Sheng Jye (2024)
Vascular endothelial growth factor (VEGF) is one of the proteins involved in the immunopathogenesis of dengue. It is highly expressed in severe dengue, where it contributes to vascular permeability and plasma leakage. Since a rapid test for predicting severe dengue is not available and the currently available methods are expensive, the development of VEGF rapid tests using lateral flow immunoassay and 3D dielectrophoresis (DEP) microfluidic chip may provide potential benefits in the management of severe dengue. In addition, it is still unclear how much VEGF and anti-VEGF therapy contribute to the effects of plasma leakage in severe dengue cases. Thus, the objectives of this study were the development of a VEGF rapid test kit and the study of the effects of VEGF and VEGF/antiVEGF treatment on endothelial cells using a vascular permeability assay and microarray gene expression profiling. Lateral flow immunoassay was able to detect VEGF levels of 10 ng/ml and above, while for 3D DEP microfluidic assay, it was more sensitive, detecting as low as 5 pg/ml of VEGF. In permeability assay, VEGF-treated endothelial cells showed higher permeability than VEGF/anti-VEGF treated and untreated cells. For microarray gene expression profiling, the genes upregulated in VEGF-treated cells were enriched for inflammatory response, regulation of endothelial barrier, regulation of nitric oxide synthesis, regulation of angiogenesis, and the NOD-like receptor signalling pathway. In conclusion, 3D DEP microfluidic chip has better sensitivity and can be designed to be more user-friendly for clinical use. VEGF treatment increased permeability across endothelial cells, while the addition of anti-VEGF reduced the degree of leakage caused by VEGF. The microarray profiling generated from treated endothelial cells showed dysregulated genes implicated in severe dengue. The prospect of using anti-VEGF antibodies to neutralise VEGF gives hope for future effective therapy to stop the progression of dengue into severe dengue.